Oxidative stress parameters in fish after subchronic exposure to acetylsalicylic acid - Zivna, Dana; Plhalova, Lucie; Praskova, Eva; Stepanova, Stanislava; Siroka, Zuzana; Sevcikova, Marie; Blahova, Jana; Bartoskova, Marta; Marsalek, Petr; Skoric, Misa; Svobodova, Zdenka (Neuro endocrinology letters, 2013)
OBJECTIVES: The aim of this study was to investigate the effects of subchronic exposure of juvenile development stages of zebrafish (Danio rerio) to acetylsalicylic acid using selected oxidative stress biomarkers. DESIGN: Toxicity test with acetylsalicylic acid was performed according to the OECD Guideline No. 215, fish D. rerio aged 30 days were used. The tested concentrations were 0.004, 0.4, 40, 120 and 250 mg.L-1, duration of the test was 28 days. Products of lipid peroxidation and antioxidant enzymes were determined as the markers of oxidative stress. RESULTS: Significantly increased glutathione S-transferase activity was found in fish exposed to acetylsalicylic acid concentrations 40, 120 and 250 mg.L-1. The highest values of glutathione reductase activity were found in the groups exposed to acetylsalicylic acid concentrations 0.4, 40 and 120 mg.L-1. In the group exposed to acetylsalicylic acid concentrations 40 mg.L-1, catalase activity was significantly higher compared to the control group. Significantly higher glutathione peroxidase activity was found in the groups exposed to acetylsalicylic acid concentrations 0.004 and 120 mg.L-1. The concentrations of TBARS were lower in fish exposed to acetylsalicylic acid at all tested concentrations compared to control. CONCLUSION: The subchronic exposure of zebrafish to acetylsalicylic acid causes an increase in activity of antioxidant and biotransformation enzymes and a decrease in lipid peroxidation.
Keywords: chemické látky znečišťující vodu; Zebrafish; Behavior, Animal; Toxicity Tests, Subchronic; oxidační stres; glutathiontransferasa; antioxidancia; Glutathione Transferase; Aspirin; látky reagující s kyselinou thiobarbiturovou; Water Pollutants, Chemical; dánio pruhované; Thiobarbituric Acid Reactive Substances; ryby; Fishes; Animals; Antioxidants; zvířata; Environmental Exposure; peroxidace lipidů; chování zvířat; Lipid Peroxidation; testy subchronické toxicity; Oxidative Stress; vystavení vlivu životního prostředí